Parathyroid Hormone Reduction Predicts Transient Hypocalcemia after Total Thyroidectomy: A Single-Center Prospective Study. (1st August 2020) - Mo, Kangnan; Shang, Jinbiao; Wang, Kejing; Gu, Jialei; Wang, Peng; Nie, Xilin; Wang, Wendong
Abstract : Objective . We performed this study to investigate the risk factors for postoperative hypocalcemia after total thyroidectomy with central lymph node dissection (CLND). Study Design . This was a single-center prospective study based on 176 consecutive patients who underwent total thyroidectomy for papillary thyroid carcinoma. Setting . Patients were recruited between January 2016 and June 2018. Subjects and Methods . Patients who underwent bilateral ( n  = 155, bilateral group) and ipsilateral CLND ( n  = 21) after total thyroidectomy were included. The preoperative and postoperative parathyroid hormone (PTH) and calcium levels were detected. The risk factors for transient hypocalcemia were identified using logistic regression analysis and receiver operating characteristic (ROC) curve analysis. Results . Fifty-one (28.98%) patients developed transient hypocalcemia, and 2 patients (1.14%) developed permanent hypoparathyroidism. There was no difference in the gender ratio or the morbidity of hypocalcemia between the patients who underwent bilateral and ipsilateral CLND. On postoperative day 1, PTH decrease was a risk factor for transient hypocalcemia in the whole cohort ( β  = 0.043, OR = 1.044, 95% CI 1.023–1.065, p < 0.001 ), bilateral group ( β  = 0.042, OR = 1.043, 95% CI 1.022–1.064, p < 0.001 ), and female patients ( β  = 0.049, OR = 1.050, 95% CI 1.026–1.075, p < 0.001 ). Tumor diameter was a risk factor for transient hypocalcemia in female patients ( β  = 0.499, OR = 1.647, 95% CI 1.003–2.704, p = 0.049 ). The ROC curve analysis illustrated that 65.58%, 71.00%, and 71.00% PTH level reduction had high accuracy in predicting transient hypocalcemia in the whole cohort, bilateral group, and female patients, respectively (AUC = 0.986, 0.987, and 0.987). Conclusion . Asymptomatic female patients with bilateral CLND and a 71.00% PTH level reduction were at a high risk of transient hypocalcemia.